(untitled) (Sains Humanika, 2016)
Social interaction among fellow travellers forms a significant component of the authentic backpacking experience. Hostel accommodation have been purposely designed to provide the kind of environment that fosters communication and interaction between backpackers. Hostel guests have typically been provided with dormitory-type rooms, shared washrooms, kitchen and living areas, thus offering less privacy but more opportunity for social interaction. Few studies to date have fully investigated how social interaction among customers actually enhance or damage the service experience. Therefore, building on previous studies on servicescapes, co-creation and backpacker tourism, a conceptual framework is developed to examine how the hostel environment could be manipulated to influence guests’ social interaction, and consequently their evaluation of the hostel service experience.